2008
DOI: 10.1186/1471-2164-9-111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis and evolution of the T cell receptor loci in the opossum Monodelphis domestica

Abstract: Background: All jawed-vertebrates have four T cell receptor (TCR) chains: alpha (TRA), beta (TRB), gamma (TRG) and delta (TRD). Marsupials appear unique by having an additional TCR: mu (TRM). The evolutionary origin of TRM and its relationship to other TCR remain obscure, and is confounded by previous results that support TRM being a hybrid between a TCR and immunoglobulin locus. The availability of the first marsupial genome sequence allows investigation of these evolutionary relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
167
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(173 citation statements)
references
References 44 publications
(75 reference statements)
4
167
1
Order By: Relevance
“…Recently the opossum genome was determined [26]. An analysis of the genome for TCR variable gene segments confirmed the location of TRA, TRB, TRD, and TRG, and surprisingly a new locus TRM that seems to be a hybrid between a TCR and immunoglobulin locus [27]. This locus is similar to the shark NAR-TCR [28].…”
Section: Origins Of Tcr and Mhc Genesmentioning
confidence: 85%
“…Recently the opossum genome was determined [26]. An analysis of the genome for TCR variable gene segments confirmed the location of TRA, TRB, TRD, and TRG, and surprisingly a new locus TRM that seems to be a hybrid between a TCR and immunoglobulin locus [27]. This locus is similar to the shark NAR-TCR [28].…”
Section: Origins Of Tcr and Mhc Genesmentioning
confidence: 85%
“…Although the structure of LRR-based antigen receptors in jawless vertebrates is quite distinct from that of Ig domain-based antigen receptors in jawed vertebrates, the overall genomic organization and the evolutionary dynamics of the VLRC locus have similarities to the genomic architecture and mode of evolution of Ig and TCR multigene families. From a genomic standpoint, the incomplete germ-line VLRC gene serves as an equivalent of the constant gene segment, whereas the clusters of different types of donor genomic cassettes represent the functional correlates of the clusters of V, D, and J gene segments of Ig or TCR loci in jawed vertebrates (20)(21)(22). Interestingly, the donor LRRencoding cassettes are not used equally for VLR assembly, in analogy with the preferential use of certain V, D, and J segments in Ig/TCR recombinations in jawed vertebrates (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their distinct sequence signatures, the different types of donor cassettes are interspersed in the VLRC-related scaffolds, a situation reminiscent of the interspersed arrangements of individual members of V gene families of Ig and TCR loci (20)(21)(22). We found evidence of multiple duplication events for the different types of donor cassettes in the VLRC locus; however, in the absence of a suitable outgroup, the number and the evolutionary timing of the apparent duplication events in the VLRC locus cannot be determined precisely.…”
Section: Discussionmentioning
confidence: 99%
“…It would have been from a V-J/C structure that modern Ig and TCR genes evolved. Although it has sometimes been suggested that the minimalist cartilaginous fish cluster represents the primordial segmental-rearranging organization, clusters could also have evolved independently, as had TCRμ genes in marsupial and monotreme mammals [23]. Additionally, cartilaginous fish TCR genes are in the translocon organization, showing that regulation and expression of genes arranged as in higher vertebrates was established by the time of chondrichthyan divergence [24, 25].…”
Section: Ig Organization In Cartilaginous Fishmentioning
confidence: 99%